129 UTEROPLACENTAL INSUFFICIENCY AFFECTS EPIGENETIC DETERMINANTS IN THE GROWTH RETARDED RAT LUNG. (10th December 2015) - O'Brien, E.; Zhao, L.; McKnight, R.; Fu, Q.; Yu, X.; Callaway, C.; Lane, R.
Abstract : Background: IUGR predisposes human infants towards chronic lung disease (CLD). Similarly, pulmonary hypoplasia and thickened alveolar septae characterize the IUGR rat (O'Brien-Ped Res 2004). The link between an early insult and a postnatal phenotype suggests an epigenetic phenomenon. Epigenetic phenomena induce persistent changes in gene expression by altering chromatin structure. Objective: We hypothesized that UPI alters determinants of chromatin structure in IUGR rat lung in association with phenotypic changes consistent with alveolar simplification. Design/Methods: Our lab uses a well characterized rat model of UPI which results in IUGR. To test our hypothesis we proposed to determine if UPI: (1) alters global and promoter specific DNA methylation; (2) alters DNA methyltransferase 1 (DNMT1), an enzyme involved in DNA methylation, mRNA or expression; (3) leads to persistent changes in DNA methylation as seen in day 21 IUGR rats; and (4) is associated with modifications of specific histone H3 sites. Results: We found that UPI increases global DNA methylation at term (D0) and at D21 in IUGR rat lung. Furthermore, DNMT1 mRNA and protein are significantly increased in D0 IUGR rat lungs (IUGR DNMT1 mRNA 135± 17% of control, p≤0.05, n=6 litters, ± SEM, IUGR DNMT1 protein 345 ± 98% of control, p≤0.05, n=5 litters, ± SEM). Interestingly, however, preliminary data suggest that promoter specific DNA methylation is decreased in both D0 and D21 IUGR rat lungs. As one would expect based upon the global DNA hypermethylation, IUGR significantly decreased acetylation of lysine 9 on histone 3 (IUGR 63.4 ± 8 % of control n=6 litters, p≤0.01, ± SEM), whereas methylation of H3 Lysine 4 and lysine 9 were not significantly altered. Conclusion: UPI modifies pulmonary epigenetic determinants in a rat model of IUGR that is characterized by alterations in gene expression and pulmonary phenotype. The response is tissue specific, in that IUGR liver and brain DNA is globally hypomethylated. We speculate that the changes in pulmonary chromatin structure represent a tissue specific response to IUGR that contributes to the postnatal changes in phenotype.